Overrepresentation of Injection Drug Use Route of Infection Among Human Immunodeficiency Virus Long-term Nonprogressors: A Nationwide, Retrospective Cohort Study in China, 1989–2016. (8th April 2019) - Han, Jing; Wu, Zunyou; McGoogan, Jennifer M; Mao, Yurong; Tang, Houlin; Li, Jian; Zhao, Yan; Jin, Cong; Detels, Roger; Brookmeyer, Ron; Lima, Viviane D; Montaner, Julio S G
Abstract: Background: Why some persons living with human immunodeficiency virus (HIV) (PLWH) progress quickly and others remain "healthy" for a decade or more without treatment remains a fundamental question of HIV pathology. We aimed to assess the epidemiological characteristics of HIV long-term nonprogressors (LTNPs) based on a cohort of PLWH in China observed between 1989 and 2016. Methods: We conducted a nationwide, retrospective cohort study among Chinese PLWH with HIV diagnosed before 1 January 2008. Records were extracted from China's national HIV/AIDS database on 30 June 2016. LTNPs were defined as those with AIDS-free, antiretroviral therapy–naive survival, with CD4 cell counts consistently ≥500/μL for ≥8 years after diagnosis. Prevalence was calculated, characteristics were described, and determinants were assessed by means of logistic regression. Potential sources of bias were also investigated. Results: Our cohort included 89 201 participants, of whom 1749 (2.0%) were categorized as LTNPs. The injection drug use (IDU) route of infection was reported by 70.7% of LTNPs, compared with only 37.1% of non-LTNPs. The odds of LTNP status were greater among those infected via IDU (adjusted odds ratio [95% confidence interval], 2.28 [1.94–2.68]) and with HIV diagnosed in settings with large populations of persons who inject drugs (1.75 [1.51–2.02] for detention centers, 1.61 [1.39–1.87] for Yunnan, 1.94 [1.62–2.31] for Guangdong, and 2.90 [2.09–4.02] for Xinjiang). Conclusions: Overrepresentation of the IDU route of infection among LTNPs is a surprising finding worthy of further study, and this newly defined cohort may be particularly well suited to exploration of the molecular biological mechanisms underlying HIV long-term nonprogression. Abstract : Persons who acquired human immunodeficiency virus (HIV) via injection drug use are surprisingly overrepresented in the largest nationwide Chinese cohort of human HIV long-term nonprogressors (LTNPs), suggesting that further investigation is warranted and may elucidate mechanisms underlying LTNP phenotypes.